Mensch Und Computer 2021 2021
DOI: 10.1145/3473856.3474007
|View full text |Cite
|
Sign up to set email alerts
|

User-Avatar Relationships in Various Contexts

Abstract: Avatars are in use when interacting in virtual environments in different contexts, in collaborative work, as well as in gaming and also in virtual meetings with friends. Therefore it is important to understand how the relationship between user and avatar works. In this study, an online survey is used to determine how the perception of an avatar changes in different contexts by relating it to existing avatar relationship typologies. Additionally, it is determined whether in each context a realistic, abstract or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Nevertheless, this use case could predict the use of immersive VR that offers a high sense of experiential presence, and users might also desire, or at least tolerate, a highly consistent avatar when interacting with others who are already very familiar with the backstage versions of one’s physical body. This view is supported by recent work by Praetorius et al, (2021, p. 279), who surveyed users on their preference for avatar representation in different contexts, following Banks’, 2015 typology of avatars. They found that realistic avatars were ‘a realistic representation form…most likely to be associated with an Avatar-as-Me relationship…particularly relevant in the context of a meeting with friends.’…”
Section: Discussionmentioning
confidence: 66%
“…Nevertheless, this use case could predict the use of immersive VR that offers a high sense of experiential presence, and users might also desire, or at least tolerate, a highly consistent avatar when interacting with others who are already very familiar with the backstage versions of one’s physical body. This view is supported by recent work by Praetorius et al, (2021, p. 279), who surveyed users on their preference for avatar representation in different contexts, following Banks’, 2015 typology of avatars. They found that realistic avatars were ‘a realistic representation form…most likely to be associated with an Avatar-as-Me relationship…particularly relevant in the context of a meeting with friends.’…”
Section: Discussionmentioning
confidence: 66%